PENGGUNAAN FAMILY THERAPY BERBASIS TEORI DUKUNGAN SOSIAL PADA PENDERITA GANGGUAN JIWA PSIKOTIK POLIMORFIK AKUT TANPA GEJALA SKIZOFRENIA - R Rapikah; N Nurjannah (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2021)
Several studies have shown that people with mental disorders are often not treated specifically by their families as they should, so family therapy is needed to deal with this. This research is a study conducted to find out whether the use of family therapy based on social support theory can be used to help families in dealing with people with mental disorders. This research is a qualitative research, in which the researcher uses a descriptive qualitative approach, namely research with a case study method or approach that focuses intensively on a family that has family member with mental disorders, namely acute polymorphic psychotic disorders without schizophrenia symptoms. The results found are that family therapy using social support theory can help families in dealing with family member with mental disorder.